3(x + 2) = 12
Dividing both sides by 3
3(x + 2)/3 = 12/3
(x + 2) = 12/3
x + 2 = 4
Subtracting 2 from both sides
x + 2 - 2 = 4 - 2
x + 0 = 2
x = 2
2007-06-17 10:39:49
·
answer #1
·
answered by psbhowmick 6
·
0⤊
0⤋
3(x+2) = 12
x+2 = 4
x=2
2007-06-17 17:41:34
·
answer #2
·
answered by Esmaeil H 2
·
0⤊
0⤋
3(x+2)=12 multiply all the things that are in the () by 3
3x+6=12
-6 -6 subtract 6
3x=6 divide by 3
x=2
2007-06-17 17:56:46
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
1. 3(x+2) = 12 (Copy Problem)
2. 3x + 6 = 12 (Multiply 3 by x and 3 by 2 to get rid of parentheses - called Distributive Property)
3. 3x + 6 - 6 = 12 - 6 (Subtract 6 from both sides)
4. x = 2 (Divide both sides by 3 to get x by itself)
2007-06-17 17:44:26
·
answer #4
·
answered by KT 2
·
0⤊
0⤋
first write the problem.
3(x+2)=12, then u have to use the distributive property.
so then it becomes,
3x+6=12, then u minus 6 from both sides,
and u get 3x=12
then u divide 3 by both sides
and then u get 2, so the answer is
x=2
2007-06-17 18:14:33
·
answer #5
·
answered by Jason R 4
·
0⤊
0⤋
x=2
heres how:
distritive property of the 3 gets you...
3x+ 6=12
minus 6 from the 12 you are left with 3x=6 divide and you get 2.
2007-06-17 17:41:15
·
answer #6
·
answered by ♥ <---- heart! 2
·
0⤊
0⤋
3x + 6 = 12
-6
3x = 6
x = 2
2007-06-17 17:54:13
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
divide 3 for both sides
x + 2 = 4
subtract 2 for both sides
x = 2
2007-06-17 17:41:55
·
answer #8
·
answered by 7
·
0⤊
0⤋
I assume you are solving for X.
First, get X alone. The order of operations tell us first to get rid of that pesky 3. So divide both sides by 3!
X+2 = 4
Then get rid of the 2, subtract both sides by 2.
X=2
2007-06-17 17:40:08
·
answer #9
·
answered by The Red King 2
·
0⤊
0⤋
x + 2 = 4
x = 2
2007-06-18 06:24:35
·
answer #10
·
answered by Como 7
·
0⤊
0⤋